Prevalence and Associated Factors to Non-Carious Cervical Lesions in Brazilian University Students: A Cross-Sectional Survey - Francielle Nunes Machado; Joice Crislainy Gomes Garcia; Nayara Silva de Almeida; Gabriela Rocha-Gomes; Dhelfeson Willya Douglas-; Olga Dumont Flecha; Patricia Furtado Gonçalves; Karine Taís Aguiar Tavano; Adriana Maria Botelho (Association of Support to Oral Health Research (APESB), 2024)
Objective: To identify the prevalence, severity, hypersensitivity, and distribution of Non-carious cervical lesions (NCCL) among university students in Brazil. Material and Methods: 179 participants answered an anamnesis with twenty questions about the presence or absence of habits associated with NCCL. The participants' teeth were evaluated to identify the presence or absence of the lesion, its classification, involved surfaces, severity, hypersensitivity, and tooth wear index. A hypersensitivity test was performed with ice water. Data were analyzed using the chi-square test and simple logistic regression (p<0.01). Results: 179 participants answered an anamnesis with twenty questions about the presence or absence of habits associated with NCCL. The participants' teeth were evaluated to identify the presence or absence of the lesion, its classification, involved surfaces, severity, hypersensitivity, and tooth wear index. A hypersensitivity test was performed with ice water. Data were analyzed using the chi-square test and simple logistic regression (p<0.01). Conclusion: The prevalence of NCCL was 15.1% and abfraction was the most frequent lesion. Premolars were the teeth most affected by non-carious cervical lesions.